Pengaruh Komunikasi yang Efektif terhadap Keberhasilahan Lobi dan Negosiasi - Ratu Reva N.; Dian Hardianti; Brizita Auliani A; Helena Angelica S; Aprilia Ningrum (Jurnal Ilmu Komunikasi, Administrasi Publik dan Kebijakan Negara, 2025)
This research examines the influence of effective communication on the success of lobbying and negotiation. Lobbying and negotiation, although differing in their approaches (lobbying is one-way persuasive, negotiation is interactive and involves bargaining), both aim to influence decisions or reach agreements. The success of both heavily relies on effective communication, which includes building relationships, understanding the interlocutor, and overcoming communication barriers. Effective communication strategies involve thorough planning, persuasive communication, conflict management, and understanding the context and interests of all parties. Literature studies show that effective communication is a key success factor, building trust, delivering persuasive messages, managing conflicts, building consensus, and understanding the needs of other parties. Persuasive, assertive, and nonverbal communication also play a crucial role in reaching mutually beneficial agreements. In conclusion, effective communication increases the chances of successful lobbying and negotiation.